PERAN LEMBAGA PERMBERDAYAAN PEREMPUAN DAN ANAK DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEJAHATAN ASUSILA (Studi Kasus Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Banda Aceh) - Rizkal Rizkal; Hanik Harianti (STIS Nahdlatul Ulama Aceh, 2021)
This study focuses on finding out how the protection of law given by Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak (P2TP2A) the city of Banda Aceh as well as the causes of increasing sexual crime in a child. As for the complex problem of this research it’s 1. How is legal protection against children as a victim of sexual crime given by P2TP2A city of Banda Aceh?. 2. What was the factor in bringing the case down Banda Aceh sexual crime?. Research which is used in this writing is a normative–empirical elements combining the normative and ampirical data elements gained in the field with a date collection interview of the P2TP2A city of Banda Aceh that is the resuld of this research is the P2TP2A child of sexual crime already In accordance with the 2014 rule of act No. 35 child protection and 2008 Qanun Aceh No. 11 on child protection. A service or protection provided by Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Banda Aceh for children of the victim rape crimes include healthcare (referrals), psychological service, legal relief service (advocacy) and security systems for victim. There are underlying factors that cause a child increase in sexual crime are family conflicts, promiscuity, druguse, an environment far from Islamic philosophy and the content of pornography that can lead to disharmony in one’s sense and passion.